Impact of Statin Therapy on Clinical Outcome in Patients With Coronary Spasm. Issue 5 (May 2016) - Ishii, Masanobu; Kaikita, Koichi; Sato, Koji; Yamanaga, Kenshi; Miyazaki, Takashi; Akasaka, Tomonori; Tabata, Noriaki; Arima, Yuichiro; Sueta, Daisuke; Sakamoto, Kenji; Yamamoto, Eiichiro; Tsujita, Kenichi; et al.
Abstract : Background: Statin therapy reduces the risk of cardiovascular events in patients with obstructive coronary artery disease. The aim of the present study was to determine the effects of statins on the prognosis of patients with coronary vasospastic angina (VSA) free of significant atherosclerotic stenosis. Methods and Results: After exclusion of 475 from 1877 consecutive patients who underwent an acetylcholine‐provocation test between January 1991 and December 2010, data of 640 VSA patients without significant organic stenosis of the remaining 1402 were analyzed retrospectively. Propensity score matching was performed to reduce the effect of treatment‐selection bias and possible confounders. The primary endpoint was major adverse cardiac events (MACE), including cardiac death, nonfatal myocardial infarction, and unstable angina. Among the study population, dyslipidemia on admission was identified in 160 of 168 (95.2%) patients of the statin group compared with only 125 of 472 (26.5%) of the no‐statin group. Of the 640 patients, 24 (3.8%) developed MACE. Multivariate Cox hazard regression analysis identified statin therapy as a significant negative predictor of MACE (hazard ratio, 0.11; 95% CI, 0.02–0.84; P =0.033). In the propensity‐score matched cohorts (n=128 each), Kaplan–Meier survival curve showed a better 5‐year MACE‐free survival rate for patients of the statin group compared to the no‐statin group (100% vs 91.7%, respectively; P =0.002). Conclusions: Statin therapy correlated with a lower rate of cardiovascular events in VSA patients free of significant organic stenosis. Statins seems to improve the prognosis of VSA patients free of significant organic stenosis.